Emergency twin births in ambulances: a qualitative case study from Sindh, Pakistan - Maqbool, Umair; Lakhiar, Tarique Quadir; Shahid, Muhammad; Mangrio, Lutaf Ali; Iqbal, Mazhar; Sarfaraz, Seema; Khaskheli, Fareed Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Emergency childbirth, particularly twin deliveries, poses profound challenges in pre-hospital contexts, where health professionals must often act swiftly under conditions of uncertainty. In rural Pakistan, where access to healthcare facilities is limited, ambulance-based deliveries have become increasingly common. This qualitative study draws on semi-structured interviews with emergency medical technicians, emergency vehicle operators, and a skilled birth attendant in Khairpur and Naushero Feroz districts of Sindh to explore the realities of managing such emergencies. The analysis revealed that variations in training, adherence to protocols, and inter-professional coordination shaped both the process and outcomes of care. Participants described the difficulties of working within constrained environments, confronting clinical complexities, and navigating cultural and gender dynamics, all while making critical decisions under pressure. Their accounts also reflected the emotional weight of these experiences, underscoring how professional background and preparedness influence responses in moments of crisis. The study points to the urgent need for structured obstetric training, strengthened infrastructure, wider integration of telemedicine, and improved collaboration among emergency personnel to safeguard maternal and neonatal health in resource-limited rural settings.